Factors Associated with glycemic control in type 2 diabetic patients at Klinik Kesihatan Jalan Masjid, Kuching, Sarawak - Amirulazman, Bin Abu Hassan (Universiti Malaysia Sarawak, (UNIMAS), 2013)
GOOd glycaemic control reduces the risk of diabetic complications. Despite this, achieving good glycaemic control remains a challenge in diabetic patients. The objective of this study is to identify the factors associated with glycaemic control among DM Type 2 patients at KK lalan Masjid, Kuching, Sarawak. A clinic-based cross-sectional study was conducted on systematically sampled 303 DM Type 2 patients on a regular follow up. Data was collected using selfadministered questionnaire and reviewing respective medical recor Data collection took place from 25 Mac 2013 till 6 May 2013. Optimal glycaemic control was defined HbA1c < 6.5%. Patients had a mean age of 54.0 (±9.2) years, 62% were females, the mean duration of since diagnosis was 7.3 (±5.3) years, 29.7% achieved optimal glycaemic control (HbA1c <6,5%), 74.7% were on oral anti diabetic agent (OAA) alone. Mean BMI for the patient was 27.3 (±4.3) kg/m2 . About 60.9 % of study participants had both Hypertension and Hyperlipidaemia. Chisquare test revealed, Employment status/working hours and Type of diabetic treatment had significant association with glycaemic control. Working 8 hours or more/day had significantly high mean HbAlc, 8.1% (±1.7%), compare to working 8 hour or less/day and unemployed group (P<O.OOO). Patients that were on OAA alone had significant lower mean HbA 1 c compare to patient on Insulin alone or on Combination treatment (Insulin and OAA). Most of the patient had positive attitude towar,d s the disease, however, there were no significant association with p' glycaemic control. The proportion of patients with sub optimal glycaemic control was high, which resulted in the development of one or more complications regardless of duration of disease. Hence, appropriate management of a patient focusing on the relevant associated factors and independent predictors of poor glycaemic control would be of great benefit. Keywords: Diabetes mellitus, factor, glycaemic control, HbAlc, Kuching